Psychological preparation and development of self-confidence in athletes Modern Pentathlon (Review) (Revista científica Olimpia, 2020)
Sport and psychology are two very related fields and, in recent decades, as well as corroborating studies increasingly being done more research in both fields relate. programs preparing the athlete for high performance have given much more importance to technical progress and to improve the physical form that development of psychological factors. However, the multiple demands of the competition, the high level of personal commitment and the need to always perform at the highest they have made the psychological preparation of the athlete becomes as necessary as they can be physical training or technical training, this research is the study of self-confidence in sport specifically in the modern pentathlon, in which an approach is from theory to provide important elements in this important issue; therefore they have been used a number of investigative methods to achieve this purpose.
Keywords: sport; psychology; self-confident; modern pentathlon